2000
DOI: 10.1002/(sici)1098-2264(200001)27:1<85::aid-gcc11>3.3.co;2-0
|View full text |Cite
|
Sign up to set email alerts
|

Interphase FISH detection of BCL2 rearrangement in follicular lymphoma using breakpoint‐flanking probes

Abstract: Rearrangement of the BCL2 gene is an important parameter for the differential diagnosis of non-Hodgkin lymphomas. Although a relatively large proportion of breakpoints is clustered, many are missed by standard PCR. A FISH assay is therefore desired. Up to now, a lack of probes flanking the BCL2 gene has limited the possibilities for a FISH assay to an approach based on colocalization of probes for BCL2 and the immunoglobulin heavy chain (IGH) locus. Intrinsically high rates of false positive nuclei and high in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
79
1
1

Year Published

2001
2001
2020
2020

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 54 publications
(86 citation statements)
references
References 31 publications
5
79
1
1
Order By: Relevance
“…Only one extranodal At the molecular level, 70-95% of follicular lymphoma are reported to contain a translocation between chromosomes 14 (IGH region) and 18 (BCL2 region). 37,38 In the present study, BCL2 rearrangement was present in 84 cases (74%; n ¼ 112). Rearrangement of the BCL6 gene, initially thought to be specifically associated with diffuse large B-cell lymphoma, is observed in 6.4% up to 14.3% of follicular lymphoma at the time of diagnosis, and may be prone to subsequent highergrade transformation.…”
Section: Discussionsupporting
confidence: 50%
“…Only one extranodal At the molecular level, 70-95% of follicular lymphoma are reported to contain a translocation between chromosomes 14 (IGH region) and 18 (BCL2 region). 37,38 In the present study, BCL2 rearrangement was present in 84 cases (74%; n ¼ 112). Rearrangement of the BCL6 gene, initially thought to be specifically associated with diffuse large B-cell lymphoma, is observed in 6.4% up to 14.3% of follicular lymphoma at the time of diagnosis, and may be prone to subsequent highergrade transformation.…”
Section: Discussionsupporting
confidence: 50%
“…4 Horsman et al (2003) investigated the cytogenetic aberrations of t(14;18) negative FL and found that the cases showing chromosome 18 duplication and BCL2-protein expression may comprise a unique subgroup of FL. 3 Recently, Guo et al (2005) reported that the t(14;18) positive group is a single tumor entity, most of which is accounted for by grades 1 and 2, whereas t(14;18) negative-FL was found to consist of distinct subgroups, majority of which is accounted for by grades 3. 5 These reports suggest that t(14;18) negative FL comprise distinct subtypes.…”
Section: Figurementioning
confidence: 99%
“…Breaks affecting the IGL locus were ruled out in the other 3 cases (Nos. [22][23][24]. DISCUSSION The accurate detection of IG illegitimate rearrangements is important for the diagnostic process and the clinical management of patients with B-cell malignancies; it is also a useful tool for discovering new genes associated with these neoplasms.…”
Section: Figure 1 (Overleaf)mentioning
confidence: 99%